Strategi Bawaslu Kota Batam dalam Minimalisir Kampanye Negatif di Media Sosial pada Pilkada Serentak 2020 - Abidin, Sholihul; Kundori, Kundori; Purwanti, Angel (Yayasan Tri Edukasi Ilmiah, 2024)
This research evaluates the effectiveness of the Batam City Bawaslu strategy in minimizing negative campaigns on social media during the 2020 Simultaneous Pilkada. This type of research uses qualitative research methods. The research results show that Bawaslu has implemented an outreach strategy through its official Instagram account, with a focus on education regarding election regulations, the role of supervisors, and the dangers of money politics. Despite these efforts, this research suggests the need for more in-depth evaluation of the effectiveness of these strategies in changing the behavior of political actors and society. Apart from that, this research also identifies several challenges faced by Bawaslu in efforts to minimize negative campaigns on social media.